Effect of Destination Image on Domestic Travelers' Satisfaction of Mandalay City - Lim, Htin Kyaw (Journal of Business & Management, 2023)
This study analyzed the effect of destination image on domestic travelers’ satisfaction of Mandalay City. Two objectives were intended for this study. The first objective was to determine the domestic travelers’ perceptions on destination image of Mandalay City. The second objective was to analyze the effect of destination image on domestic travelers’ satisfaction of Mandalay City. In this study, destination image was measured by four dimensions: namely natural environment, cultural environment, social environment, and infrastructure. To attain these objectives, both primary and secondary data were utilized, and the data was gathered from travelers who have visited Mandalay City in the last two years. Convenience sampling was used to collect data for the application from a total of 385 travelers. The findings of this study showed that most domestic travelers’ perception of Mandalay City is based on its cultural environment. In addition, two dimensions of destination image, namely, cultural environment and infrastructure have significant positive effects on domestic travelers’ satisfaction. Therefore, in order to satisfy travelers, the authority should maintain and develop various traditional architecture and cultural heritage atmosphere and the local community and stakeholders should also maintain and develop good quality infrastructure such as quality road and public transport systems.